Attachment and savouring on mothers of children with Autism Spectrum Disorder - Lu, Sharrie Yuyi (2018)
Autism Spectrum Disorder (ASD), characterised by socio-communicative deficits, has been identified as one of the most common diagnoses among young children in Singapore. Parents of children with ASD often face challenges in interpreting their child’s needs, with mothers being more susceptible than fathers to elevated levels of parenting stress and poorer wellbeing as a consequence. As such, this study explores Savouring as an intervention to tap on one’s ability to attend to positive emotions and memories, helping mothers of children with ASD to recognise and cherish moments of sensitive care towards their child, thus improving parent-child relationship and satisfaction. 32 mothers were randomly assigned to either personal or relational savouring conditions; focusing on positive personal moments or moments shared with their child, respectively. Research also found mothers’ attachment styles to be predictive of the quality of mother-child interactions as well as the security of the child’s attachment. Therefore, it would be beneficial to investigate the influence of maternal attachment styles in its fundamental dimensions of avoidance and anxiety on parenting satisfaction and positive affect after undergoing the savouring tasks. Other factors frequently documented in mothers of children with ASD such as parenting stress and perceived social support are also included in the analysis. Results found significant increase in parenting satisfaction in mothers with high attachment avoidance in the personal savouring condition. Also, mothers perceiving moderate to high social support is associated with significant decrease or increase in positive affect after the savouring tasks. Further implications and recommendations are also discussed.